Antiproliferative activity of quercetin and prima-1met against hct-116 and hct-15 colon cancer cells - CHANDRA SEKHAR PASULA,; DR. SAVITHIRI SHIVAKUMAR,; YASODHA LAKSHMI T,; Y RAJA RATNA REDDY,; MANI RAJESH,; RAMAMOORHTY S, (International Journal of Pharma and Bio Sciences, 2017)
Quercetin is a plant flavonoid with significant chemopreventive and anticancer activity against many cancer types. The aim of the present study is to evaluate the anticancer properties of quercetin in synergism with the selected p53 activator PRIMA-1MET in human colon cancer cells with different p53 status. Colon cancer cells HCT-116 (wild type p53), HCT-15(mutant p53) were treated with different concentrations of both drugs alone and in combination and the effect was evaluated in cell viability and apoptosis assays. Cell viability - MTT assay was conducted with different doses of quercetin (10-300 µM) and PRIMA-1MET (5-75 µM) for 24 and 48 hours. Significant dose and time dependent reduction in cell viability was observed. High antiproliferative effect was observed at 48 hours treatment. Quercetin and PRIMA-1MET combination effect was checked in both cell viability and apoptosis assay by DAPI staining method. The highest antiproliferative effect was 64.8 at 50+10 µM (Que+PRI) concentration in HCT-116 and 80.8 at 50+50 µM in HCT-15 cells. Combination effect was evaluated by CompuSyn software, synergistic effect was observed at 50+10 µM (Que+PRI) concentration in both the cancer cells. Similar combination effect was observed in apoptosis assay, significant increase in apoptotic cells was observed in (Que+PRI) combination treatment than individual. 50+10 µM concentration of quercetin and PRIMA-1MET is an effective synergistic combination in both the selected cancer cells.Clear synergistic anticancer activity was observed with the selected drug combinations in both colon cancer cells (mutant and wild type p53) in all the assays due to the targeting of multiple activators and effectors which regulates cell proliferation and apoptosis.